Roll-to-roll stack and lamination of gas diffusion layer in multilayer structured membrane electrode assembly. (January 2020) - Chen, Jiankui; Jiang, Xi; Tang, Wei; Ma, Liang; Li, Yiqun; Huang, YongAn; Yin, Zhouping
A membrane electrode assembly is the core component of a proton-exchange membrane fuel cell stack. It consists of multilayer structured membranes which are flexible, heterogeneous and have variable cross section. To improve the efficiency of membrane electrode assembly processing and manufacturing, a roll-to-roll system with gas diffusion layer is designed. By peeling the protective membrane and the upper and lower gas diffusion layers' hot-pressing, proton-exchange membrane is manufactured into a five-layer catalyst-coated membrane. Then, the catalyst-coated membrane is manufactured into membrane electrode assembly by multilayer membrane breakpoint die-cutting and laying-off. The system integrates multiple key technologies, including roll-to-roll precise feeding, gas diffusion layer multi-degree accurate operation and multichannel temperature control, to realize the precise positioning of flexible multilayer membrane and brittle gas diffusion layer. The tension inhomogeneity and critical wrinkling tension are modeled for web traveling in the continuous roll-to-roll manufacturing equipment. The proposed roll-to-roll stack and lamination system effectively combines discontinuous hot-pressing, die-cutting, laying-off technics to realize the high-efficiency manufacturing of membrane electrode assembly.